2000
DOI: 10.1080/026783700750051658
|View full text |Cite
|
Sign up to set email alerts
|

The role of stress and social support in Sick Building Syndrome

Abstract: Sick Building Syndrome (SBS) involves seemingly healthy individuals experiencing long-lasting symptoms of physical distress in their work settings and is estimated to exist in 20 to 30 % of all work settings in the USA. We examined diŠ erences in stress, social support and both physical and psychological symptoms reported by hospital personnel working in known SBS sites in Halifax, Nova Scotia (n¯297) with control employees working in relatively SBS-free settings (n¯228). We found that employees reporting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…Earlier studies suggested that factors such as indoor dust, ventilation rates, and microbiological and psychological characteristics also were related to the prevalence of SBS (Skov et al, 1987;Mendell and Smith, 1990;Bauer et al, 1992;Ryan and Morrow, 1992;Seppanen et al, 1999;Mendelson et al, 2000, Mendell et al, 2002Assoulin-Daya et al, 2002;Seppanen and Fisk, 2002). A large-scale study concerning the contribution of these factors to SBS is in progress.…”
Section: Vocs and Changes Of Subjective Symptomsmentioning
confidence: 99%
“…Earlier studies suggested that factors such as indoor dust, ventilation rates, and microbiological and psychological characteristics also were related to the prevalence of SBS (Skov et al, 1987;Mendell and Smith, 1990;Bauer et al, 1992;Ryan and Morrow, 1992;Seppanen et al, 1999;Mendelson et al, 2000, Mendell et al, 2002Assoulin-Daya et al, 2002;Seppanen and Fisk, 2002). A large-scale study concerning the contribution of these factors to SBS is in progress.…”
Section: Vocs and Changes Of Subjective Symptomsmentioning
confidence: 99%
“…Some SBS studies have linked job stressors such as high workload and low levels of support with higher prevalence of physical symptoms (e.g., Eriksson et al, 1996;Marmot et al, 2006;Mendelson et al, 2000;Stenberg et al, 1994). In a review of relevant literature, Lahtinen et al (1998) found higher workload, lower job control, poorer social relationships, lower job satisfaction, and higher job stress to be consistently related to higher SBS symptoms.…”
Section: Physical Symptomsmentioning
confidence: 99%
“…Many researchers have examined the role of social support in promoting the psychological well‐being of employees (e.g. Beehr et al, 2003; De Jonge, Dormann, Janssen, Dollard, Landeweerd, & Nijhuis, 2001; Mendelson, Catano, & Kelloway, 2000). Social support may be defined as behaviors that are intended to assist others and sources of support may include a variety of people (e.g.…”
Section: Introductionmentioning
confidence: 99%